Fracture properties of a refractory high-entropy alloy: In situ micro-cantilever and atom probe tomography studies. (February 2017) - Zou, Y.; Okle, P.; Yu, H.; Sumigawa, T.; Kitamura, T.; Maiti, S.; Steurer, W.; Spolenak, R.
Abstract: Most refractory high-entropy alloys (HEAs) are brittle and suffer from limited formability at ambient temperature. Previous studies imply that grain boundaries affect their fracture behavior, but quantitative studies on the fracture properties of body-centered-cubic HEAs are scarce. Here, using in situ micro-cantilever tests, we show that the fracture toughness of a bi-crystal HEA, Nb25 Mo25 Ta25 W25, is one order of magnitude lower than that of single crystalline ones. Atom probe tomography of the bi-crystal HEA reveals element segregation and formation of oxides and nitrides at grain boundaries, suggesting that minimizing grain boundary segregation is critical to improving fracture properties in refractory HEAs. Graphical abstract: